Evaluation Activity of Boiled Aqueous Extract of Broccoli Flower Plant (Brassica Oleraceae L. Var. Italic) And Albendazole Drug Against the Protoscolices in Vitro - Nabaa Zahid Sabri Shani Al-Hasnawi 1, Ahmed Khudhair Al-Hamairy2 , Huda Jasim M. Altameme2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study aimed to testing the efficacy of the boiled aqueous extract of broccoli flowers andalbindazole drug against the viability of protoscolices In vitro. The results showed the percentage of viabilityof the protoscolices were 94% at zero time then become (0%) after nine days after the start of the experimentwhen using culture media of (Kreb ringers and the cyst fluid ) (4 : 1) respectively as control group forcomparison. . the aqueous extract of boiled for the flower of (Brassica oleraceae) with concentration of 300mg / ml showed most effective in eliminating viability of protoscolices after 168 hours and the albendazoledrug after 120 hours at percentage 0 % for both.